2004
DOI: 10.1109/tip.2004.833105
|View full text |Cite
|
Sign up to set email alerts
|

Region Filling and Object Removal by Exemplar-Based Image Inpainting

Abstract: A new algorithm is proposed for removing large objects from digital images. The challenge is to fill in the hole that is left behind in a visually plausible way. In the past, this problem has been addressed by two classes of algorithms: 1) "texture synthesis" algorithms for generating large image regions from sample textures and 2) "inpainting" techniques for filling in small image gaps. The former has been demonstrated for "textures"--repeating two-dimensional patterns with some stochasticity; the latter focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
2,676
1
27

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 2,849 publications
(2,716 citation statements)
references
References 23 publications
12
2,676
1
27
Order By: Relevance
“…As exemplars, patch-based methods are currently the focus of attention of the computer vision community in various domains such as texture synthesis (Efros and Freeman, 2001), in-painting (Criminisi et al, 2004), restoration (Buades et al, 2005), and single-frame super resolution (Protter et al, 2009). In each of these domains, patch-based methods have been the subject of intensive investigation because they exhibit very high performance despite their simplicity.…”
Section: Introductionmentioning
confidence: 99%
“…As exemplars, patch-based methods are currently the focus of attention of the computer vision community in various domains such as texture synthesis (Efros and Freeman, 2001), in-painting (Criminisi et al, 2004), restoration (Buades et al, 2005), and single-frame super resolution (Protter et al, 2009). In each of these domains, patch-based methods have been the subject of intensive investigation because they exhibit very high performance despite their simplicity.…”
Section: Introductionmentioning
confidence: 99%
“…In [20], a patch priority based inpainting is suggested that extends known image patches to the missing parts of the image. A non-local exemplar based method is suggested in [60], where the missing patches are estimated as means of selected non-local patches.…”
Section: Sparse Bleed-through Inpaintingmentioning
confidence: 99%
“…Image inpainting, which refers to filling in missing or corrupted regions in an image, is a well studied and challenging topic in computer vision and image processing [19,20]. In image inpainting, the goal is to find an estimate for those regions in order to reconstruct a visually pleasant and consistent image [21].…”
Section: Introductionmentioning
confidence: 99%
“…This concept was picked up and further analyzed Wei and Levoy [WL00] and justified in terms of probability theory by Levina and Bickel [LB06]. Criminisi et al applied the concept to inpainting problems like object removal in [CPT04].…”
Section: Exemplar-based Inpaintingmentioning
confidence: 99%
“…The algorithms in [EL99,WL00] are greedy methods for the computation of a suitable correspondence map, since each pixel in the inpainting domain is visited only once. As it was shown in [CPT04] the quality of the result heavily depends on the order in which the pixels are processed. The two results in the Subfigures 1c and 1d are actually obtained by the same method of comparing patches, but just visiting the pixels in a different order.…”
Section: Introductionmentioning
confidence: 98%